2021
DOI: 10.5435/jaaos-d-20-00288
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Online Reviews of Orthopaedic Surgeons and Orthopaedic Practices Using Natural Language Processing

Abstract: Background: There is growing interest in measuring and improving patient experience. Machine learning–based natural language processing techniques may help identify instructive themes in online comments written by patients about their healthcare provider. Separating individual surgeon and orthopaedic office reviews, we analyzed themes that are discussed based on the rating category, the association with review length, the number of people posting more than one review for a surgeon or office, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Patient experience reflects quality of care from the patient’s perspective, hence these are important data that can teach us about what creates an (un)satisfying experience. 35 …”
Section: Part Ii: Three Forms Of Machine Learning To Aid Clinical Decmentioning
confidence: 99%
“…Patient experience reflects quality of care from the patient’s perspective, hence these are important data that can teach us about what creates an (un)satisfying experience. 35 …”
Section: Part Ii: Three Forms Of Machine Learning To Aid Clinical Decmentioning
confidence: 99%
“… 2020 , Langerhuizen et al. 2020 ). 3rd, we included only studies in high-impact orthopedic journals.…”
Section: Discussionmentioning
confidence: 99%
“…2nd, the IBM tone analyzer was trained on a large Twitter customer-support dataset. Although previously used in the context of medical studies, the reliability of the analyzer for medical journals is untested (Ottenhoff et al 2018, Rajesh et al 2018, Bakker et al 2019, Karacic et al 2019, Black et al 2020, Langerhuizen et al 2020. 3rd, we included only studies in high-impact orthopedic journals.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that care and compassion are vital elements when it comes to patient satisfaction. Patient-clinician relationships and patient experiences seem to be related to communication and a lack of perceived empathy by the surgeon [ 16 •]. NLP and sentiment analysis were used to analyze free-text comments compared with a national inpatient survey by Greaves et al Over 6000 free-text comments posted online during the same period as the survey were analyzed.…”
Section: Introductionmentioning
confidence: 99%